A Review on the Role of IT Application Controls in Mitigating Data Discrepancies in Government Financial Reporting - Andi Kartika Kusnasriyanti; Muchriana Muchran; Ramly Ramly (Westscience Press, 2026)
This systematic literature review examines the role of Information Technology Application Controls (ITACs) in mitigating data discrepancies within government financial reporting. Recognizing that reliable financial data is a cornerstone of public accountability and fiscal governance, this review synthesizes empirical and conceptual research to analyze the function of automated controls in ensuring data accuracy, completeness, and validity. The findings, derived from a rigorous PRISMA-guided analysis of 22 studies, elucidate the causal mechanisms through which ITACs operate, namely, via preventive (e.g., input validation), detective (e.g., anomaly detection), and corrective (e.g., automated reconciliation) pathways. However, the literature specifically cataloging the most frequent ITAC types in government systems remains limited, instead highlighting the growing role of advanced technologies like blockchain and AI. The review further identifies significant implementation challenges unique to the public sector, including fragmented IT infrastructures, resource constraints, and bureaucratic resistance. Critical success factors for effective ITAC deployment emphasize strong top-management support, staff capacity building, and alignment with established governance frameworks like COBIT. The study concludes that mitigating data discrepancies requires a holistic strategy where technical controls are synergistically supported by robust governance and continuous organizational learning to enhance the integrity and reliability of public financial statements.